Theology of ministry : a Reformed contribution to an ecumenical dialogue - Borght, Ed. A. J. G. van der, 1956- (Studies in Reformed theology, 2007)
Theology of ministry has always been a controversial issue in the relation between churches, especially with its juridical approach that concentrated on authority. In recent decades the secularization and individualization in the Western world have intensified the challenge to reformulate the mission of the church and its ministries. Building on the Reformed theology of the 16th century (Zwingli, Calvin and confessions) and on the results of the ecumenical convergence on ministry (BEM) in the 20th century, this study presents building blocks for a renewed theology of ministry in the 21st century.